2001
DOI: 10.1016/s0960-9822(01)00373-6
|View full text |Cite
|
Sign up to set email alerts
|

A natural variability in the proline-rich motif of Nef modulates HIV-1 replication in primary T cells

Abstract: In the infected host, the Nef protein of HIV/SIV is required for high viral loads and thus disease progression. Recent evidence indicates that Nef enhances replication in the T cell compartment after the virus is transmitted from dendritic cells (DC). The underlying mechanism, however, is not clear. Here, we report that a natural variability in the proline-rich motif (R71T) profoundly modulated Nef-stimulated viral replication in primary T cells of immature dendritic cell/T cell cocultures. Whereas both Nef va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…These target T-cells are fully permissive for HIV replication despite the lack of classical T-cell activation markers, suggesting that Nef selectively induces a low state of activation. Importantly, mutation of the Nef PXXP motif blunts its ability to boost HIV-1 replication in co-cultures of immature dendritic cells and autologous T-lymphocytes (51) and prevents the modulation of TCR-induced actin remodeling (this study). We therefore hypothesize that this newly identified modulation of IS maturation helps Nef to generate a moderate TCR signal optimized for HIV-1 production.…”
Section: Discussionmentioning
confidence: 72%
“…These target T-cells are fully permissive for HIV replication despite the lack of classical T-cell activation markers, suggesting that Nef selectively induces a low state of activation. Importantly, mutation of the Nef PXXP motif blunts its ability to boost HIV-1 replication in co-cultures of immature dendritic cells and autologous T-lymphocytes (51) and prevents the modulation of TCR-induced actin remodeling (this study). We therefore hypothesize that this newly identified modulation of IS maturation helps Nef to generate a moderate TCR signal optimized for HIV-1 production.…”
Section: Discussionmentioning
confidence: 72%
“…Importantly, Nef-mediated increase of the cellular activation state can be detected in target T cells already prior to integration of the incoming viral genome (72). Such activation was recently shown to be relevant in a primary cell coculture model of immature dendritic cells and autologous T cells, where efficient virus replication requires Nef and correlates with its ability to induce signaling (25,45,50).…”
mentioning
confidence: 99%
“…Importantly, the PxxP motif of Nef that is a prerequisite for Pak activation is required for the optimal spread of HIV in primary cells (25,44,58). Furthermore, one study reported a correlation between the association of Nef with Pak activity and disease progression in SIV-infected macaques (61).…”
mentioning
confidence: 99%
“…Moreover, Nef activates signaling cascades that increase levels of viral replication in primary T cells (11,14,44). Finally, Nef increases levels of Gag in detergent-resistant microdomains (lipid rafts) at the plasma membrane to enhance the infectivity of progeny virions (53).…”
mentioning
confidence: 99%